Impact of gender on the prognosis of carotid body tumor after surgical resection - Huanrui Hu; Yuwei Xiang; Bin Huang; Ding Yuan; Yi Yang; Jichun Zhao (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Carotid body tumors (CBTs) are rare neuroendocrine neoplasms, but the prognosis of patients with resected CBTs has seldom been elucidated. This study was conducted to investigate the association between variables, especially sex, and the prognosis of carotid body tumor resection. Methods This was a large-volume single-center retrospective cohort study. Patients who were diagnosed with CBTs between 2009 and 2020 at our center were analyzed retrospectively. Their preoperative, surgical, and follow-up data were collected, and the association between variables and outcomes of CBT resection was assessed by correlation analysis, multivariate logistic regression, and multivariate Cox regression as appropriate. Results A total of 326 patients (66.6% were females) were included. Males developed larger CBTs than females (4.3 ± 1.8 cm vs. 3.8 ± 1.4 cm, P = .003). Males were more likely to develop succinate dehydrogenase B (SDHB) mutations (P = .019) and had worse relapse-free survival rates (P = .024). Although tumor size and Shamblin classification had positive relationships with neurological complications and intraoperative blood loss, they did not affect the overall survival rate of patients, which was only influenced by remote metastasis (P = .007) and local recurrence (P = .008). Conclusions Compared to females, males with CBT resection were found to have more SDHB mutations and worse relapse-free survival rates, which may lead to the deterioration of prognosis. Tumor size and Shamblin classification cannot predict the overall survival rate of patients with excised CBTs. Graphical abstract